2015
DOI: 10.1155/2015/581437
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis, a Nonenhanced CT Diagnosis?

Abstract: Purpose. Retrospectively evaluate the density of cerebral venous sinuses in nonenhanced head CTs (NCTs) and correlate these with the presence or absence of a cerebral venous sinus thrombus (CVST). Materials and Methods. Institutional review board approval was obtained and informed consent waived prior to commencing this retrospective study. Over a two-year period, all CT venograms (CTVs) performed at our institution were retrieved and the preceding/subsequent NCTs evaluated. Hounsfield Units (HUs) of thrombus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
1
17
2
1
Order By: Relevance
“…The finding of hyperattenuation in a thrombosed sinus is in accordance with previously reported findings [11,12,[19][20][21]. In previously published material different cutoffs for HU have been proposed ranging from 62 to 70 [12,[19][20][21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding of hyperattenuation in a thrombosed sinus is in accordance with previously reported findings [11,12,[19][20][21]. In previously published material different cutoffs for HU have been proposed ranging from 62 to 70 [12,[19][20][21].…”
Section: Discussionsupporting
confidence: 90%
“…Patient age is one important consideration when deciding imaging strategy, since computed tomography (CT) exposes the patient to ionizing radiation [18]. Previous studies have reported on the diagnostic utility of nonenhanced head computed tomography (neCT) to suspect CVST due to high density in the sinuses [11,12,[19][20][21][22]. Despite previous reports suggesting the applicability of neCT to accurately identify acute CVST, other methods such as magnetic resonance imaging (MRI) or CT venography (CTV) are recommended to verify the diagnosis of CVST.…”
Section: Introductionmentioning
confidence: 99%
“…The average HU of vessels containing a thrombus was 68 ± 1.56, which was significantly higher than that of normal vessels 52 ± 0.28. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Non-contrast computed tomography (NCCT) is widely used as the initial imaging modality of choice in neurological emergencies 2,1013 . Increased attenuation of cerebral sinus venous structures is considered the only direct finding of acute CVST in the NCCT 11,14,15 . Increased sinus attenuation has the advantage of being objective and easily calculated, while being able to diagnose CVST in the acute stage, when treatment is most likely to be effective and associated with favorable outcome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased sinus attenuation has the advantage of being objective and easily calculated, while being able to diagnose CVST in the acute stage, when treatment is most likely to be effective and associated with favorable outcome 13 . The drawback of this sign is the influence of various factors like serum hematocrit level and dehydration on sinus attenuation that may lead to false positive results and inappropriate disposition 2,10,11,15 . The possibility of changing the intracranial vasculature computed tomography (CT) attenuation under the influence of variable factors is a long-held unestablished belief.…”
Section: Introductionmentioning
confidence: 99%